A proteção dos consumidores como direito fundamental e as negativas de cobertura em contratos securitários : cláusulas limitativas versus cláusulas abusivas à luz da jurisprudência - Dahinten, Augusto Franke (2015)
This essay aims to analyze the incidence of consumer law in the insurance contracts, mainly regarding the discussion between the limitative and abusive clauses, in light of the jurisprudence. With this goal, it starts, in the first half, with the analysis of the theoretical fundamentals that underlie the objective of this research. It begins with the presentation of the consumer protection as a fundamental right and its insertion in the Brazilian legislative context. Next, it exams the insurance contracts, its concept, its purpose and importance, its characteristics and features, as well as the actors that figure in the domestic insurance market. Following, are commented some of the most important contractual aspects, including the evolution and the transformations that the Contract Law suffered, the principles that govern the contractual bonds and the main rules related to consumer contractual protection. In the second part, it’s worked on some of the major coverage negatives involving insurance contracts in the light of the national jurisprudence, which is done three stages, subdivided according to the insurance modalities. In each part, it’s worked on the general aspects of each controversy, including the arguments summoned by the parties, followed by the jurisprudential understandings. All with the end goal of analyzing which understandings and fundaments are presented in these kinds of demands.